2020
DOI: 10.1038/s41467-020-19556-5
|View full text |Cite
|
Sign up to set email alerts
|

The Polycomb group protein Ring1 regulates dorsoventral patterning of the mouse telencephalon

Abstract: Dorsal-ventral patterning of the mammalian telencephalon is fundamental to the formation of distinct functional regions including the neocortex and ganglionic eminence. While Bone morphogenetic protein (BMP), Wnt, and Sonic hedgehog (Shh) signaling are known to determine regional identity along the dorsoventral axis, how the region-specific expression of these morphogens is established remains unclear. Here we show that the Polycomb group (PcG) protein Ring1 contributes to the ventralization of the mouse telen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 72 publications
(100 reference statements)
0
33
0
Order By: Relevance
“…The SHH concentration gradient ultimately governs the patterning of the central nervous system along the dorsoventral domains. Regulation of SHH expression extends beyond its direct release from the notochord, and includes its repression by bone morphogenic proteins (BMP) and WNT signaling molecules [ 51 , 52 , 53 ]. SHH has antagonistic interactions with the dorsally expressed BMP and WNT signaling proteins [ Figure 1 B], which will fully define the limits of the range of each domain.…”
Section: Shh Signaling During Embryogenesismentioning
confidence: 99%
“…The SHH concentration gradient ultimately governs the patterning of the central nervous system along the dorsoventral domains. Regulation of SHH expression extends beyond its direct release from the notochord, and includes its repression by bone morphogenic proteins (BMP) and WNT signaling molecules [ 51 , 52 , 53 ]. SHH has antagonistic interactions with the dorsally expressed BMP and WNT signaling proteins [ Figure 1 B], which will fully define the limits of the range of each domain.…”
Section: Shh Signaling During Embryogenesismentioning
confidence: 99%
“… For reverse transcription (RT) and qPCR and RNA-seq analyses, freeze the cell pellet with liquid N 2 and store at −80°C. 10,000 cells are enough for RT-qPCR and usual RNA-seq analyses, and 1,000 cells are used for Quartz-seq analysis ( Eto et al., 2020 ; Kuwayama et al., 2020 ; Sakai et al., 2019 ). Pause point: Store the cell pellets at −80°C for more than 1 year.…”
Section: Step-by-step Methods Detailsmentioning
confidence: 99%
“…We can also directly sort the cells into the 1.5 mL tube, including cell stock solution in step 26. We used 10,000 cells for H3K27me3 and 100,000 cells for Ring1B CUT&Tag ( Eto et al., 2020 ).
Figure 2 Gating strategies for isolation of neural progenitors and neurons from the neocortex of Nestin-d4Venus or wild-type embryos (A) Neocortical cells of Nestin-d4Venus –/– or Nestin-d4Venus +/– embryos at E14 were dissociated and subjected to FACS analysis as described previously ( Sakai et al., 2019 ).
…”
Section: Step-by-step Methods Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…The source regions of morphogen ligands have been well identified; however, the mechanism that determines which areas have active The distribution of H3K27me3 and Ring1B were highly regionspecific. [56] Cleavage under targets and tagmentation (CUT&Tag) analysis, a recently developed method for epigenome profiling, [61] of isolated NPCs from the dorsal midline, neocortex, and GE revealed that accumulation of H3K27me3 and Ring1B at the Bmp4 and Bmp7 gene loci in the neocortex and GE increased relative to the dorsal midline. [56] Because the expression levels of Wif1 and Dkk2 in the telencephalon of Ring1A/B neu-KO were not different (data not shown), the deposition of H3K27me3 at the Wif1, Dkk2, Foxg1, and Pax6 gene loci may be midbrain-specific.…”
Section: What Regulates the Spatial And Temporal Specificity Of Gene Repression By Pcg?mentioning
confidence: 99%